SOSIALISASI PENGEMBANGAN WEBSITE SEKOLAH SEBAGAI SARANA PROMOSI DAN EDUKASI DI SMK TERPADU CITRA BANGSA KOTA TARAKAN - Fadllullah, A.; Pradana, A.; Harto, D.; ,, Mulyadi; Arsianti, R. W.; ., Rudy (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana Mengabdi, 2022)
In the scope of online media, SMK Terpadu Citra Bangsa, Yayasan Roudhotus Sakinah has never socialized student admissions with information about schools and others through electronic promotion media (official website). Even though this SMK has a major in automotive engineering which has a large market share in Tarakan City, but many people do not know. Therefore, based on these problems, we propose PKM activities about “Socialization of School Website Development as a Promotional and Educational in the SMK Terpadu Citra Bangsa, Tarakan City”. In determining the outputs/results of this activity using the PAP (Project Action Plan) method with 3 scopes of activity. For the site survey, it is obtained that the school already has internet access, but does not yet have an official school website. The target for display and website development was achieved around 100%, because all menus were successfully created and provided on the website. As for the target participants achieved in this socialization of 79%. They are even able to fill in data and information into the school's web with their respective author accounts. It is hoped that this activity can provide a development for school promotion media and make it easier for the public to find information about this vocational school, so that the interest in attending this school is getting bigger.   Keywords: Promotion, Education, website, SMK, Tarakan City